Electrolytic conductances and related properties of solutions of some acids and salts in acetone - Brookes, Hugh Clive (Department of Chemistry, 2015)
Although a thorough investigation of various methods of preparing pure, anhydrous acetone has been made (cf. Sadie), no investigations of methods for determining the moisture content of this solvent have previously been described. A solvent with a consistently low water content is essential for electrochemical measurements. Accordingly an extensive study of moisture content determination in acetone-was made. A modified Karl Fischer titration procedure was found to be most suitable for the very low moisture contents of the acetone used in this work. All A.C. conductance measurements made using two platinised electrodes are, in some degree, liable to errors due to polarization, end effects and the state of the electrode surfaces. Several workers have also found errors due to the presence of finely divided platinum, such as adsorption of electrolyte on the colloidal platinum, the shaking effect and catalysis of reactions in solution. These errors are reduced by using lightly platinised or bright platinum electrodes, but polished electrodes give rise to increased polarization errors. In this work conductance measurements were made using a new four-electrode A.C. potentiometer, which employs bright platinum electrodes enabling conductance measurements to be carried out in acetone without recourse to platinisation, thus avoiding errors due to the presence of platinum black, contact resistances of electrodes and the like. The measurements on this apparatus were shown to be independent of frequency using aqueous potassium chloride solutions, and the accuracy of the results was tested using aqueous sodium chloride solutions. Perchlorates have been considered by some investigators (e.g. Ross Kane) to be strong electrolytes in acetone solutions and other workers (e.g. Accascina and Schiavo) found the alkali perchlorates to be weak electrolytes. The approximate limiting ionic conductances calculated by these last named workers were at variance with those of other investigators (e.g. Kraus). It therefore appeared that a study of the conductances of solutions in acetone of perchloric acid and some of its salts by the new potentiometric method would be advantageous. The conductances of three alkali perchlorates and the previou3ly unknown conductances in acetone of ammonium perchloratey pure anhydrous perchloric acid and lithium chloride were measured by the potentiometric method. Limiting equivalent conductances and dissociation constants were calculated for all the electrolytes and the results discussed. These electrolytes were, in general, found to be relatively weak in acetone, although perchloric acid is considerably stronger than hydrochloric acid. The conductance results indicated that the potentiometric method should be generally applicable to electrolyte solutions in all solvents, and can be used to advantage in all cases influenced by the errors previously mentioned. It is generally recognized that interpretation of conductance data and the development of the theory of electrolyte solutions is seriously hindered by the lack of transport data in non-aqueous solvents. Transference measurements were undertaken using a conductimetric moving boundary method, and a limiting transport number for the anion constituent of potassium thiocyanate was obtained in acetone. This is the first reasonably accurate limiting transport number to have been measured in acetone. From the equivalent conductance data of this work, and the literature, the first limiting ionic conductances in acetone have been calculated and the results discussed. The limiting conductance of the hydrogen ion 101cm² ohm-¹ equiv-¹ , was not found to be anomalous, as for example, in water. Anions were found to have generally higher conductances than cations, which is consistent with the view that cations are in general, more solvated than anions in dipolar aprotic solvents. Conductance results of numerous workers have indicated considerable uncertainty about the entities present in acetone solutions of hydrogen chloride. In order to add to existing knowledge, tracer diffusion coefficients of hydrogen chloride in acetone solutions were measured at 15⁰ , 25⁰ and 35⁰C over a range of concentrations using hydrogen chloride labelled with chlorine -36. The capillary tube method was used, and concentrations were measured by a scintillation counting procedure. Complete interpretation of the results is impossible in the light of present knowledge, but they appear to be consistent with suggestions, based on conductance measurements in this system, that hydrogen chloride polymers may be present.